Dialogs and Reflections on the Communications in the Unidad Popular. Chile, 1970-1973 [Diálogos y Reflexiones Sobre Las Comunicaciones en la Unidad Popular. Chile, 1970-1973] - Rivera-Aravena, C (Universidad Complutense de Madrid, 2015)
The following article examines the debate that aroused concerning communications during the government of Popular Unity. The Center of Studies of the National Reality (CEREN), of the Catholic University of Santiago, established a precedent proposing new approaches - different to the dominant ones - that were later transformed into paradigms for Communications. Armand Mattelart, Michèle Mattelart and Mabel Piccini, in fact, opened the debate demonstrating and questioning the lack of vision of the left in this matter. Thus the lack of communication policies from the government did not prevent the development of new experiences conditioned by the revolutionary context.
Keywords: Armand Mattelart; Center for studies of the national reality; Michèle Mattelart y Mabel Piccini; Revolutionary communications; Unidad popular